The Influence of Digital Marketing and Brand Image on the Performance of Moi Kelapa Gading Square MSME Product Quality Moderated - Kustiadi Basuki; Annisa Nur Husni (Budapest International Research and Critics University, 2022)
Research objectives this is to find out how to maintain a MSME business by means of a digital marketing strategy that is currently more accessible to many people. The research method is quantitative, by using google form and distributing to respondents. The results of this study prove that digital marketing has a positive and significant influence on performance in MSMEs and product quality has a positive and significant impact on brand image which is moderated by performance in MSMEs.